INTEGRASI NILAI-NILAI HADIS WAKAF PRODUKTIF DALAM PENGUATAN MODEL BISNIS SOSIAL ISLAMI - Farida Aprianti; Muhammadiyah Amin; La Ode Ismail Ahmad; Muhammad Rusdin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
This study examines the principles of productive waqf from the perspective of the Prophet's hadith and analyzes its integration into strengthening the Islamic social business model. Using a thematic (maudhū‘ī) hadith approach, it explores the concept of ḥabs al-aṣl wa tasaddaq bi al-ṯamarah as the foundation of productive waqf. The findings reveal eight value indicators within the hadiths that form the basis for developing an Islamic social economy: retention of principal assets, sustainability and distribution of benefits, sharia compliance, trustworthiness and professionalism of the naẓir, social welfare orientation, freedom from haram elements, and sincerity of intention. These values, when integrated into Islamic social business practices, form three main pillars: financial independence, measurable social benefits, and trust-based governance that drives systemic change. This integration results in an economic management model based on maqāṣid al-syarī‘ah, balancing worship objectives with economic sustainability. Consequently, from a hadith perspective, productive waqf functions not merely as a religious philanthropic instrument, but as a paradigm for socio-economic transformation capable of building community independence and equitable wealth distribution.